Comparative Analysis of Metabolite Changes in Huangjiu During Different Aging Periods Using HRMS Metabolomics - Yue E; Zhuang Wang; Hongbin Guo (Metabolites)
Background: Huangjiu, a traditional Chinese fermented alcoholic beverage, exhibits a multifaceted chemical profile comprising diverse metabolites, such as lipids, amino acids, and phenolic compounds. The age of the wine is an important indicator of its quality and is a primary reference for purchasing decisions. Methods: This study employs high-resolution mass spectrometry to perform metabolomics analysis on Huangjiu of varying ages and uses multivariate statistical analysis to characterize the chemical features of different types of Huangjiu. This research investigates the Huangjiu aged from 3 to 30 years, involving samples of five different aging periods. Results: A total of 415 compounds were detected across all samples, including 147 differential metabolites. It was observed that, as the aging of Huangjiu increased, the relative content of most metabolites showed a rising trend. However, 19 metabolites, mainly lipids and lipid-like molecules, decreased in concentration over time. This finding highlights significant differences in metabolite composition among Huangjiu of different ages. Furthermore, 19 characteristic differential metabolites were predicted as markers for distinguishing Huangjiu of different ages. Conclusions: This study provides theoretical and material foundations for quality control, health benefits, and industrial development of Huangjiu.